Pengaruh Modal Usaha dan Jasa Perbaikan Motor Terhadap Pendapatan Bengkel - Fafan Titaley, Meiske Marisa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the effect of working capital and repair services on workshop income in Fakfak Regency. The research data consist of working capital, number of repair services, and workshop income over the past five years. The analysis method used is multiple linear regression with the help of SPSS. The results show that working capital has a positive and significant effect on workshop income, repair services have a positive and significant effect on workshop income, and both simultaneously have a significant effect on income. Repair services are the most dominant factor influencing workshop income. The implication of this research is that increasing working capital and optimizing repair services are essential strategies for improving workshop income.